Community Service Increases One-Year-Old Preschool Children's Interest in Learning Orchid Type (SPS) ll - Prayoga, Abi; Perkasa, Dhana Rachmatulloh; Usman, Ridhatul; Zahrafaini, Ravechia; Fernando, Johan; Yuaniko, Yuaniko (Santoso Academy Network, 2024)
This community development is intended so that children can be independent in their daily learning and can increase their interest in learning. The methods used are 1) study assistance, 2) quizzes, 3) tests/practice questions, and 4) interaction/question and answer. At the end of the session, students who can answer the quiz given will get a reward. The results of this service show that children are happy, have increased interest in learning, and are comfortable when studying, both with subjects, learning materials, and the learning used, namely through the interactive quiz learning method. immunity service activities aimed at increasing the interest in learning among one-year-old preschool children, specifically focusing on orchid types, have significant managerial implications. These activities can foster early cognitive development and curiosity in young children by integrating engaging, hands-on experiences with botanical education. By involving parents and educators in the process, the program promotes a collaborative approach to early childhood education, ensuring that learning is both fun and impactful.